Pembuatan Website Sebagai Media Promosi Wisata Pulau Mubut - Swono Sibagariang; Yeni Rokhayati; Afdhol Dzikri; Siskha Handayani; Metta Santiputri; Agung Riyadi; Nur Zahrati Janah; Muhamad Sahrul Nizan (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2021)
The development of information technology that is fast and easy to use, allows someone to quickly publish certain objects. Information technology also contributes to the introduction and existence of an area that has tourism potential. If the tourism potential of an area is not carried out properly and correctly, it will not be known by many people. As the island of Mubut should be able to do. Mubut Island, which has a lot of potentials, can be a promotional tool to attract local and foreign tourists, especially tourism. One of the problems that arise from tourism management lies in the lack of good promotional strategies and the absence of clear and accurate sources of information about the potential of Mubut island tourism. Utilizing a website as a promotional medium is a good choice to achieve this. Therefore, in this service activity, we will build a website that can later be used as a means of promotion and training will be conducted in managing website content for the operator appointed as the person in charge of the website.